Vericiguat Modulates Osteoclast Differentiation and Bone Resorption via a Balance between VASP and NF-κB Pathways. (16th June 2022) - Sun, Kaiqiang; Kong, Fanqi; Lin, Feng; Li, Fudong; Sun, Jingchuan; Ren, Changzhen; Zheng, Bing; Shi, Jiangang
Abstract : Bone homeostasis has been a dynamic equilibrium between osteoclasts (OCs) and osteoblasts (OBs). However, excessive activation of OCs could disturb the bone homeostasis. As a result, effective medical interventions for patients are greatly demanding. NO/guanylate cyclase (GC)/cGMP signaling cascade has been previously reported to regulate bone metabolism, and GC plays a significantly critical role. Vericiguat, as a novel oral soluble guanylate cyclase (sGC) stimulator, has been firstly reported in 2020 to treat patients with heart failure. Nevertheless, the biological effects of Vericiguat on the function of OCs have not yet been explored. In this present study, we found that Vericiguat with the concentration between 0 and 8 μ M was noncytotoxic to bone marrow-derived monocyte-macrophage lineage (BMMs). Vericiguat could enhance the differentiation of OCs at concentration of 500 nM, whereas it inhibited OC differentiation at 8 μ M. In addition, Vericiguat also showed dual effects on OC fusion and bone resorption in a dose-dependent manner. Furthermore, a molecular assay suggested that the dual regulatory effects of Vericiguat on OCs were mediated by the bidirectional activation of the I κ B- α /NF- κ B signaling pathway. Taken together, our present study demonstrated the dual effects of Vericiguat on the formation of functional OCs. The regulatory effects of Vericiguat on OCs were achieved by the bidirectional modulation of the I κ B- α /NF- κ B signaling pathway, and a potential balance between the I κ B- α /NF- κ B signaling pathway and sGC/cGMP/VASP may exist.